THE IMPACT OF E-SERVICE QUALITY ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS MEDIATING VARIABLE (CASE STUDY OF TRAVELOKA IN PONTIANAK) - KONSTANTIA, STELLA KONSTANTIA B1024141005 (Jurnal Manajemen Update, 2018)
This study aimed to investigate the direct and indirect impact of electronic service quality towards customer satisfaction and customer loyalty on Traveloka in Pontianak. The respondents in this study are Pontianak citizen who ever access to Traveloka website and did transaction in Traveloka for the last 6 months. Primary data was gathered using online questionnaire base on 100 respondents of Traveloka’s customers in Pontianak. The data was analyzed based on multiple linear regression analysis using SPSS version 22.0.Data processing results shows that the electronic service quality had a significant impact on customer satisfaction and customer loyalty. The electronic service quality includes Reliability, Website Design, Responsiveness, and Privacy. The findings of this study also proved that Customer Satisfaction mediated the relation between Electronic Service Quality and Customer Loyalty. Keywords: electronic service quality, reliability, website design, responsiveness, privacy, customer satisfaction, customer loyalty BIBLIOGRAPHIES Ainiyah, N., Deliar, A. & Virtriana, R. (2016). The Classical Assumption Test to Driving Factors of Land Cover Change in The Development Region of Northern Part of West Java. The International Archives of the Photogrammerly, Remote Sensing and Spatial Information Sciences, 205-210.Alba, J.W. & Hutchinson, J. W. (2007). Dimensions of Consumer Expertise. The Journal of Consumer Research, 13(4), 411-454.Alias, R. A., Halim, M. S. A. & Mansor, N. (2016). The Mediating Effect of E-Customer Satisfaction between E-Commerce Service Quality and E-Customer Loyalty in Malaysian Hotel Industry. Journal of Applied Environmental and Biological Sciences, 6(3S), 55-61Anderson, R.E. & Srinivasan S.S. (2003). Satisfaction and E-loyalty: a Contingency Framework, Psychology and Marketing, 20(2), 123-138Anggarwal. Y. P. (2008). Science of Educational Research A source Book: Nirmal Book Agency.Ariff, M. S. M., Yun, L. O., Zakuan, N. & Ismail, K. (2013). The Impacts of Service Quality and Customer Satisfaction on Customer Loyalty in Internet Banking. Procedia-Social and Behavioral Sciences, 81, 469-473.Asadpoor, S. & Aboifazli, A. (2017). Effect of Electronic Service Quality on Customer Satisfaction and Loyalty Saderat Bank’s Customers. International Journal of Scientific Study, 5(4), 407-411Asadpoor, S. & Aboifazli, A. (2017). Effect of Electronic Service Quality on Customer Satisfaction and Loyalty Saderat Bank’s Customers. International Journal of Scientific Study, 5(4), 407-411Asgari, N., Ahmadi, M. H., Shamlou, M., Farokhi, A. R., & Farzin, M. (2014). Studying The Impact of E-Service Quality on E-Loyalty of Customers in the Area of E-Banking Services. Journal of Management and Sustainability, 4(2), 126-133Asika, N. (2005). Research Methodology in Behavioral Sciences: Lagos. Longman Publishing Limited banks and Other Financial Institution Act 1991.Ataburo, H., Muntaka, A. S. & Quansah, E. K. (2017). Linkages among E-Service Quality, Satisfaction, and Usage of E-Services within Higher Educational Environments. International Journal of Business and Social Research, 7(3), 10-26Auka, D.O., Bosire, J.N., & Matern, V. (2013). Perceived Service Quality and Customer Loyalty in Retail Banking in Kenya. British Journal of Marketing Studies, 1, 32-61.Barnes, S.J. & Vidgen, R. T. (2006). Data Triangulation and Web Quality Metrics: A Case Study in E-Government. Information & Management, 43(6), 767-777.Baum, David, 1999. E-Commerce.  New jersey: oracle corp.Behjati, S., Nahich, M. & Othaman, S.N. (2012). Interrelation between E-service Quality and E-Satisfaction and Loyalty. European Journal of Business and Management, 4(9), 75-85Bertea, P. E. & Moisescu, O. I. (2011). Perceived Risk, Price and Online Travel Agencies: Does Price Always Matter. Management & Marketing Journal, University of Craiova, Faculty of Economics and Business Administration, 0(1), 32-42Bertozzi, F. & Krishnan, S. (2017). The Effect of Customer Satisfaction Constructs on Generation Y e-Loyalty in Malaysia. Management 2017, 7(3), 110-117Boshoff, C. & Gray, B. (2004). The Relationships between Service Quality, Customer Satisfaction and Buying Intentions in The Private Hospital Industry. South African Journal of Business Management, 35(4), 27-37.Bowen & Chen (2001). The Relationship between Customer Loyalty and Customer Satisfaction, International Journal of Contemporary Hospitality Management, 13(5), 213-217Brown, H. D. (2004). Language Assessment: Principles and classroom practices. White Plains, NY:  Pearson Longman.Caruana, A., & Ewing, M.T. (2009). How Corporate Reputation, Quality, and Value Influence Online Loyalty. Journal of Business Research, 30, 1-8.Chang, H.H. & Wang, H.W. (2008). The Relationships among E-Service Quality, Value, Satisfaction, and Loyalty in Online Shopping. European Advances in Consumer Research, 8, 10-14.Chang, H.H., Wang, Y. H. & Yang, W. Y. (2009). The impact of E-service Quality, Customer Satisfaction and Loyalty on E-Marketing: Moderating effect of Perceived Value. Total Quality Management & Business Excellence, 20(4), 423-443.Chen, P. T. & Hu, H. H. (2010). The Effect of Relational Benefits on Perceived Value in Relation to Customer Loyalty: An Empirical Study in the Australian Coffee Outlets Industry. International Journal of Hospitality Management, 29(3), 405-412.Chen, Y. H., Hsu, I. C., & Lin, C. C. (2010). Website Attributes that Increase Consumer Purchase Intention: A Conjoint Analysis. Journal of Business Research, 63 (9-10), 1007-1014.Cheung, M. K. & Lee, K. O. (2005). Research Framework for Consumer Satisfaction With Internet Shopping. Working Papers on Information Systems, 1-17Choi, J.W., Seol, H.J., Lee, S.J., Cho, H.M., Park, Y.T. (2008). Customer Satisfaction factors of mobile commerce in Korea. Internet Research, 18(3), 313-335Chow, K. M. (2017). E-Service Quality: A Study of Online Hotel Booking Websites in Hong Kong. Asian Journal of Economics, Business and Accounting, 3(4), 1-13.Chung, K. & Shin, J. (2010). The Antecedents and Consequences of Relationship Quality in Internet Shopping. Asia Pacific Journal of Marketing and Logistics, 22(4), 473-491Collier, J. E. & Bienstock, C. C. (2006). Measuring Service Quality in E-Retailing. Journal of Service Research, 8(3), 260-275Creswell, J. W. (2008). Educational Research: Planning, Conducting, and Evaluating Quantitative and Qualitative Research. Pearson/Merrill Prentice Hall.Cyr, D. & Smith, H. T. (2004). Localization of Web Design: An Empirical Comparison of German, Japanese, and US Web Site Characteristics. Journal of The American Society for Information Science and Technology, 55(13), 1-10Cyr, D., Kindra, G. S. & Dash, S. (2008). Web Site Design, Trust, Satisfaction and E-Loyalty: The Indian Experience. Online Information Review, 32(6), 773-790Doost, H.V. & Ashrafi, A. (2014). Relationship of Online Service Quality with Customer Satisfaction in Internet Banking Case Study: Pasargad Bank. International Journal of Economy, Management and Social Sciences, 3(1), 130-135Doost, H.V. & Ashrafi, A. (2014). Relationship of Online Service Quality with Customer Satisfaction in Internet Banking Case Study: Pasargad Bank. International Journal of Economy, Management and Social Sciences, 3(1), 130-135Durmus, B., Ulusu, Y. & Erdem, S. (2013). Which Dimensions Affect Private Shopping E-Customer Loyalty. Procedia – Social and Behavioral Sciences, 99, 420-427Flavian, C., Guinaliu, M., & Gurrea, R. (2006). The Role Played by Perceived Usability, Satisfaction and Consumer Trust on Website Loyalty. Information & Management, 43, 1-14.Flint, D. J. , Blocker, C. P., & Boutin, P. J. (2011). Customer Value Anticipation, Customer Satisfaction and Loyalty: An Empirical Examination. Industrial Marketing Management, 40, 219-230Friedman, B., Kahn, P. H. Jr., Howe, D.C. (2000). Trust Online. Communication of the ACM December, 34-40.Ganguli, S. & Roy, S. K. (2011). Generic Technology-based Service Quality Dimension in Banking: Impact on Customer Satisfaction and Loyalty. International Journal of Bank Marketing, 29(2), 168-189.Ghane, S., Fathian, M. & Gholamian, M.R. (2011). Full Relationship among E-satsifaction, E-trust, E-service Quality and E-loyalty: The Case Study of Iran E-banking. Journal of Theoretical and Applied Information Technology, 33(1), 1-6.Ghozali, I. (2001). Aplikasi Analisis Multivariate dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Ghozali, I. (2007). Aplikasi Analisis Multivariate dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Ghozali, I. (2013). Aplikasi Analisis Multivariate dengan Program IBM SPSS 21 Update PLS Regresi. Semarang: Badan Penerbit Universitas Diponegoro.Glaveli, N., Petridou, E., Liassides, C., & Spathis, C. (2006). Bank Service Quality: Evidence from five Balkan countries. Managing Service Quality: An International Journal , 16, 380-394.Godwin, J., Udo, G. J., Bagchi, K.K. & Kirs, P. J. (2010). An Assessment of Customers’ E-service Quality Perception, Satisfaction, and Intention. International Journal of Information Management, 3(6).Graeff, T. R. & Harmon, S. (2002). Collecting and Using Personal Data: Consumers’ Awareness and Concerns. Journal of Consumer Marketing, 19(4), 302-318Grewal, D., Iyer, G. R., & Levy, M. (2004). Internet Retailing: Enablers, Limiters, and Market Consequences. Journal of Business Research, 57(7), 703-713Gronroos, C. (2000). Service Management and marketing: A Customer Relationship Management Approach, Wiley, Chichester.Hamid, N.A.A. (2008). The Relative Importance of Trust and Usable Website Design in Building E-Loyalty Intention on Internet Banking. Communication of the IBIMA, 3, 101-113.Hair, J.F., Hult, G. T. M., Ringle, C. M., and Sarstedt, M. (2017). A Primer on Partial Least Squares Structural Equation Modeling (PLS-SEM)., 2nd Ed., Thousand Oakes, CA: Sage.Heim, G. R. & Field, J. M. (2007). Process Drivers of E-service Quality: Analysis of Data From an Online Rating Site. Journal of Operations Management, 25, 962-984.Herr, P.M., Kardes, F.R. & Kim, J. (1991). Effects of Word of Mouth and Product Attribute Information on Persuasion: An accessibility-diagnosticity perspective. Journal of Consumer Research, 17, 454-462.Hsu, S. H. (2008). Developing an Index for Online Customer Satisfaction: Adaptation of American Customer Satisfaction Index. Expert Systems with Applications, 34(4), 3033-3042.Iddrisu, A. M., Nooni, I. K., Fianko, K. S., & Mensah, W. (2015). Assessing the Impact of Service Quality on Customer Loyalty: A Case Study of The Cellular Industry of Ghana. British Journal of Marketing Studies, 3(6), 15-30.Jeon, M.H.M. & Jeong, M.Y. (2017). Customers’ Perceived Website Service Quality and Its Effects on E-loyalty. International Journal of Contemporary Hospitality Management, 29(1), 438-457Joseph, M., Sekhon, Y., Stone, G., & Tinson, J. (2005). An Exploratory Study on The Use of Banking Technology in The UK: A Ranking of Importance of Selected Technology on Consumer Perception of Service Delivery Performance. International Journal of Bank Marketing, 23(5), 397-413Jun, M., Yang, Z. & Kim, D. (2004). Customer’s Perceptions of Online Retailing Service Quality and Their Satisfaction. International Journal of Quality & Reliability Management, 21(8), 817-840Kandampully, J & Suhartanto, D (2000). Customer Loyalty in The Hotel Industry: The Role of Customer Satisfaction and Image. International Journal of Contemporary Hospitality Management, 12(6), 346-351Kim, Y. J., Jin, B. H., Swinney, J. L. (2009). The Role of E-tail Quality, E-Satisfaction and E-Trust in Online Loyalty Development Process. Journal of Retailing and Customer Service, 16, 239-247Kolsaker, A.,  Kelley, L. L. & Choy, P. C. (2004). The Reluctant Hong Kong Consumer: Purchasing Travel Online. International Journal of Consumer Studies, 28(3), 295-304Kotler, P. & Keller, K. (2012). Marketing Management. Upper Saddle River, N.J.: Prentice Hall.Kumar, V., Aksoy, L., Donkers, B., Venkatesan, R., Wiesel, T. and Tillmanns, S.(2010). Undervalued or Overvalued Customers: Capturing total customer engagement value. Journal of Service Research, 13(3), 297-310.Kumar, V., Petersen, J.A. & Leone, R. P. (2010). Driving Profitability by Encouraging Customer Referrals: who, when, and how. Journal of Marketing, 74(5), 1-17.Lam, S. Y., Shankar, V., Erramilli, M.K., & Murthy, B. (2004) Customer Value, Satisfaction, Loyalty, and Switching Costs: An illustration From a Business-to-Business Service Context. Journal of the Academy of marketing Science, 32, 293-311.Law, R. & Cheung, C. (2006). A Study of Perceived Importance of the Overall Website Quality of Different Classes of Hotels. International Journal of Hospitality Management, 25(3), 525-531.Lau, T.C., Kwek, C.L. & Tan, H. P. (2011). Airline e-Ticketing Service: How e-Service Quality and Customer Satisfaction Impacted Purchase Intention. International Business Management, 5(4), 200-208Lee, G. G. & Lin, H. F. (2005). Customer Perceptions of E-Service Quality in Online Shopping. International Journal of Retail & Distribution Management, 33(2), 161-176Lee, S.C., Barker, S., & Kandampully, J. (2003). Technology, Service Quality, and Customer Loyalty in Hotels: Australian Managerial Perspectives. Managing Service Quality: An International Journal, 13(5), 423-432Li, Hongxiu and Suomi, Reima. (2009). A Proposed Scale for Measuring E-service Quality. International Journal of u- and e-Service, Science, and Technology, 2(1), 13-17Liang, T. P. & Lai, H. J. (2002). Effect of Store Desing on Consumer Purchases: An Empirical Study of On-line Bookstores. Information & Management, 39(6), 431-444Lin, C. C. (2003). A Critical Appraisal of Customer Satisfaction and E-Commerce. Managerial Auditing Journal, 18(3), 202-212Lin, H. H. & Wang, Y. S. (2006). An Examination of The Determinants of Customer Loyalty in Mobile Commerce Contexts. Information & Management, 43, 271-282Lim, K.S. & Razzaque, M. A. (1997). Brand Loyalty and Situational Effects. Journal of International Consumer Marketing, 9, 95-115Lin, M. C., Chiu, Y.P., Huang, C. H. & Wu, Y.P. (2017). Exploring the Impact of Service Quality on Online Customer Loyalty. International Journal of e-Education, e-Business, e-Management and e-Learning, 7(4), 230-238Liu, C., Du, T. C., & Tsai, H. (2009). A Study of The Service Quality of General Portals. Information & Management, 46, 52-56Liu, Yuping. (2007). The Long-Term Impact of Loyalty Programs on Consumer Purchase Behavior and Loyalty. Journal of Marketing, 71(4), 19-35.Lovelock, C., Laure, H., Wright, K. (2011). Service Marketing Management. PT Indeks (Gramedia Group): Jakarta.Madu, C. N., & Madu, A. A. (2002). Dimension of E-Quality. International Journal of Quality and Reliability Management, 19(3), 246-258Malhotra, N. K. (2010). Introduction: Analyzing Accumulated Knowledge and Influencing Future Research (Review of Marketing Research Volume 7). Emerald Group Publishing Limited, 13-28.Mandić, Milan. (2009). Privacy and Security in E-commerce. Journal of The Faculty of Economics & Business – Zagreb, Marketing Department and CROMAR, 21(2), 247-260Marianna, S. (2009). E-Service Quality and Web 2.0: Expanding Quality Models to Include Customers Participation and Inter-Customer Support. The Service Industries Journal,  29(10).Mengi, P. (2009). Customer Satisfaction with Service Quality: An Empirical Study of Public and Private Sector Banks. IUP Journal of Management Research, 8(9), 7-17.Minh, N.V., Huu, N.H. (2016), The Relationship between Service Quality, Customer Satisfaction and Customer Loyalty: An Investigation in Vietanmese Retail Banking Sector. Jour;nal of Cempetitiveness, 8(2), 103-116Monsuwe, T. P., Dellaert, B. G. C., & Ruyter, K. D. (2004). What Drives Consumers to Shop Online? A Literature Review. International Journal of Service Industry Management. 15(1), 102-121.Naserieh, N. & Loh, A. (2014). A Study of the Factors Affecting E-Customers Loyalty of Parsian Bank in Iran. International Conference on Business, Law and Corporate Social Responisiblity Oct 1-2, 50-54Nuseir, M. & Madanat, H. (2015). 4Ps: A Strategy to Secure Customers’ Loyalty via Customer Satisfaction. International Journal of Marketing Studies, 7(4), 78-87Nyoni, S., Chiguvi, D. & Nhlane, P. (2017). The Impact of Electronic Service Quality on Customer Satisfaction in The Botswana Commercial Banking Sector. International Journal of Economics, Commerce and Management, 5(4), 390-400Ojasalo, Jukka. (2010). E-Service Quality: A Conceptual Model. International Journal of Arts and Sciences, 3(7), 127-143Oliver, R. L. (1997), Satisfaction: A Behavioral Perspective on the Consumer, New York, NY: McGraw-Hill.Papadomichelaki, X. and Mentzas, G. (2012). E-GovQual: A Multiple-Item Scale for Assessing E-Government Service Quality. Government Information Quarterly, 29, 98-109.Parasuraman, A., Zeithaml, V. A., & Berry, L. L. (1985). A Conceptual Model of Service Quality and Its Implications for Future Research. Journal of Marketing, 49, 41-50.Parasuraman, A., Zeithaml, V. A., & Berry, L. L. (1988). Servqual: A Multiple-item Scale for Measuring Consumer Perceptions of Service Quality. Journal of Retailing, 64(1), 12-40.Parasuraman, A., Zeithaml, V. A., & Malhotra, A. (2002). Service Quality Delivery Through Web Sites: A Critical Review of Extant Knowledge. Journal of The Academy of Marketing Science, 30(4), 362Parasuraman, A., Zeithaml, V. A., & Malhotra, A. (2005). E-S-Qual: A Multiple Item Scale for Assessing Electronic Service Quality. Journal of Service Research, 7(3), 213-233Pather, S. & Usabuwera, S. (2010). Implications  of e-Service Quality Dimensions for The Information System Function. Proceedings of the 43nd Hawaii International Conference on System Sciences (HICSS-43), 11Patterson, P. G., Johnson, L. W. & Spreng, R. A. (1997). Modeling The Determinants of Customer Satisfaction For Business-To-Business Professional Services. Journal of The Academy of Marketing Science, 25(1), 4-17Polit, D. & Hungler, B. (1993). Nursing Research: Methods, Appraisal, and utilisation: Third edition. Philadelphia: Lippincott.Pratminingsih, S. A., Lipuringtyas, C. & Rimenta, T. (2013). Factors Influencing Customer Loyalty Toward Online Shopping. International Journal of Trade, Economics, and Finance, 4(3), 104-110Priyatno, D. (2012). Cara Kilat Belajar Analisis Data dengan SPSS 20. Yogyakarta: Andi Offset.Ranaweera, C. & Prabhu, J. (2003). The Influence of Satisfaction, Trust, and Switching Barriers on Customer Retention in a Continuous Purchasing Setting. International Journal of Service Industry Management, 14(4), 374-395.Rosen, S. (2001). Sticky Website  is Key to Success. Communication World, 18(3), 36-37Rusk, R.T. & Zahorik, A.J. (1993). Customer Satisfaction, Customer Retention, and Market Share. Journal of Retailing, 69(2), 193-215.Samritwong, N. (2012). Satisfaction for E-Commerce Affecting Customer Loyalty: A Case Study of Internet Users in Bangkok. International Conference on Applied Mathematics, Finance, and Economics (ICAMFE’2012), 89-95Santos, J. (2003). E-Service Quality: A Model of Virtual Service Quality Dimensions. Managing Service Quality: An International Journal, 13(3), 233-246Santoso, S. (2010). Statistik Multivariat. Jakarta: PT Elex Media Komputindo.Santouridis, I., Trivellas, P. & Reklitis, P. (2009). Internet Service Quality and Customer Satisfaction: Examining Internet Banking in Greece. Total Quality Management & Business Excellence, 20(2), 223-239Sarwono, J. (2007). Analisis Jalur Untuk Riset Bisnis dengan SPSS. Yogyakarta: Penerbit AndiShankar, V., Smith, A. K. & Rangaswamy, A. (2003). Customer Satisfaction and Loyalty in Online and Offline Environments. Intern. J. of Research in Marketing, 20, 153-175,Shoemaker, S. & Lewis, R.C. (1999). Customer Loyalty: the future of hospitality marketing, International Journal of Hospitality Management, 18, 345-370Silverman, G. (2001). How and Why to Research Word of Market. Quicks Marketing Research Review.Solimun. 2011. Analisis Multivariat Pemodelan Struktural Metode Partial Least Square – PLS. Malang: Penerbit CV Citra Malang.Sugiyono. 2010. Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Sugiyono. 2016. Metode Penelititan Kuantitatif, Kualitatif dan R&D. Bandung: PT Alfabet.Syahrul, N. J., & Sidi, J. (2005). Improving Product Display of E-Commerce Website Through Aesthetics, Attractiveness, and Interactivity. In the Proceedings of the 4th International Conference on IT in Asia, CITA 2005, Kuching, Sarawak, Malaysia, 23-27.Tam, L. M. (2012). The Moderating Role of Perceived Risk in Loyalty Intentions: an Investigation in a Service Context. Markeing Intelligence & Planning, 30(1), 33-52.Tan, F.B., Lung, L., Xu, Y. (2009). A Study of Web Designer Criteria for Effective Business to Customer (B2C) Websites using the repertory grid technique, Journal of Ecommerce Research , 10(3), 155-177Tandon, U., Kiran, R. &  Sah, A. (2017). Analyzing Customer Satisfaction: Users Perspective Towards Online Shopping. Nankai Business Review International, 8(3), 266-288Tsoukatos, E. & Rand, G. K. (2006). Path Analysis of Perceived Service Quality, Satisfaction and Loyalty in Greek Insurance. Managing Service Quality: An International Journal, 16(5), 501-519.Ullah, A., Raza, M. & Chander, S. (2016). Effect of Perceived Quality of Service on Customer Loyalty: A Case of Pearl Continental Hotel Services. City University Research Journal, 6(1), 81-100Visansakon, T. & Prougestaporn, P. (2015). Influencing of e-Service Quality to e-Loyalty of Thai Consumers toward Online Hotel Booking. Journal of Economics, Business and Management, 3(9), 908-911Wahab, S., Zahari, A.S.M., Momani, K.A., Nor, N.A.M. (2011). The Influence of Perceived Privacy on Customer Loyalty in Mobile Phone Services: An empirical Research in Jordan. IJCSI International Journal of Computer Science Issues, 8(2),45-52.Wang, Y. S., Wang, Y. M., Lin. H. H. & Tang, T. I. (2003). Determinants of User Acceptance of Internet Banking: An Imperical Study. International Journal of Service Industry Management, 14(5), 501-519.Wolfinbarger, M. & Gilly, M. (2000). Consumer Motivation for Online Shopping. AMCIS 2000 Proceedings, 112, 1362-1366Wolfinbarger, M. & Gilly, M. C. (2003). eTailQ: Dimensionalizing, Measuring and Predicting Etail Quality: Journal of Retailing, 79, 183-198.Yang, Z. & Fang, X. (2004). Online Service Quality Dimensions and Their Relationships with Satisfaction: A Content Analysis of Customer Reviews of Securities Brokerage Services. International Journal of Service Industry Management, 15(3), 302-326.Yang, Z. & Jun, M. (2002). Consumer Perception of E-service Quality: From Internet Purchase and Non-Purchaser Perspectives. J. Bus. Strategies, 19, 19-41Yen, C. H. & Lu, H. P. (2008). Effects of E-service Quality on Loyalty Intention: An Empirical Study in Online Action. Managing Service Quality: An International Journal, 18(2), 127-146.Zafar, M., Zaheer, A., Rahman, S.U. & Rehman, K.U. (2010). Impact of Online Service Quality on Customer Satisfaction in Banking Sector of Pakistan. African Journal of Business Management, 5(30), 11786-11793Zeithaml, V.A, Parasuraman, A., & Malhotra, A. (2002). Service Quality Delivery through Web Sites: A Critical Review of Extant Knowledge. Journal of the Academic of Marketing Science, 30(4), 358-371.Zhang, X. & Prybutok, V.R. (2005). A Consumer Perspective of E-Service Quality. IEEE Transactions on Engineering Management, 52(4), 461-477.Zhu, F. X., Wymer, W., & Chen, I. (2002). IT-based Services and Service Quality in Consumer Banking. International Journal of Service Industry Management, 13(1), 69-90.